2007
DOI: 10.1007/s00531-007-0269-9
|View full text |Cite
|
Sign up to set email alerts
|

The Oligo-/Miocene Qom Formation (Iran): evidence for an early Burdigalian restriction of the Tethyan Seaway and closure of its Iranian gateways

Abstract: In the central Iranian Esfahan-Sirjan and Qom basins sedimentation of the Oligo-/Miocene Qom Formation took place on extensive mixed carbonate-siliciclastic ramps. During this time, both basins were positioned at the Eurasian margin of the Tethyan Seaway, which connected the western and eastern regions of the Tethys Ocean at least until the late Burdigalian. During the so-called Terminal Tethyan Event the Tethyan Seaway was then closed due to the collision of the African/Arabian and Iranian/Eurasian plates. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(191 citation statements)
references
References 24 publications
9
179
3
Order By: Relevance
“…The co-occurrence of this species with M. polymorpha which is seen in stratigraphical records (only from Indo-Pacific) highly support the assumption of a probable marine connection between Indo-Pacific and Mediterranean Tethys in Burdigalian time in the region (Harzhauser et al, 2002;Reuter et al, 2009, Qom formation, Iran). …”
Section: Resultssupporting
confidence: 65%
“…The co-occurrence of this species with M. polymorpha which is seen in stratigraphical records (only from Indo-Pacific) highly support the assumption of a probable marine connection between Indo-Pacific and Mediterranean Tethys in Burdigalian time in the region (Harzhauser et al, 2002;Reuter et al, 2009, Qom formation, Iran). …”
Section: Resultssupporting
confidence: 65%
“…Therefore we suggest that, prior to approximately 14 Ma, a relatively deep seaway connected the Indian Ocean and the proto-Mediterranean, allowing the production of TISW. Moreover, the termination of TISW production during the MMCT (Woodruff and Savin, 1989;Wright et al, 1992;Kennett, 1994, 1995) suggests a middle Miocene age for the final closure of the Tethys seaway, which is consistent with oceanic palaeontological data (Rögl, 1999;Harzhauser et al, , 2009Reuter et al, 2009). Our results are in disagreement with the study of Hüs-ing et al (2009), who suggested that a connection between the Mediterranean Sea and the Indian Ocean still existed at 11 Ma.…”
Section: Timing Of the Eastern Tethys Seaway Closurecontrasting
confidence: 58%
“…Finally, stratigraphic and oceanic palaeontological data indicate that the Mediterranean Basin and the Indian Ocean were intermittently connected until at least the middle Miocene (Rögl, 1999;Harzhauser et al, , 2009Okay et al, 2010). The consensual view is that, after the initial collision between AfroArabia and Eurasia, the remaining eastern Tethys seaway was not floored by oceanic crust, and the re-opening phases were mainly due to sea-level changes (Rögl, 1999;Harzhauser et al, , 2009Allen and Armstrong, 2008;Hüsing et al, 2009;Reuter et al, 2009;Okay et al, 2010). The final closure of the Tethys seaway after the Langhian transgression (ca.…”
Section: N Hamon Et Al: Tethys Seaway Closure and Middle Miocene CLmentioning
confidence: 99%
“…Comparable assemblages are described from the upper Chattian of the central Iranian Qom Formation (Mandic 2000;Harzhauser 2004;Reuter et al 2007) and along the entire northern coast of the Western Tethys (Harzhauser et al 2002). A relation to the Central Paratethys is indicated by the occurrence of Ringicardium buekkianum, which is known from the Lower Egerian ( in contrast, represents ties with the echinoid fauna of the Lower Indus Basin.…”
Section: Biostratigraphic Results Of the Muş Basinmentioning
confidence: 97%